Collaborative Classrooms: The Impact of Peer Instruction on Secondary School Students’ Learning Outcomes in Chemistry - Okunuga, Rachael Olatoun; Adeleke, Saheed Bimbola (FKIP-Universitas Riau, 2024)
This study investigated the impact of peer instruction on students’ achievement in senior secondary school chemistry in Lagos State, Nigeria. The study population comprised secondary school chemistry students in the state. It adopted a quasi-experimental design and used the Chemistry Achievement Test and questionnaire to obtain information from the students. The data collected were analysed using mean, percentages and standard deviation, while inferential statistics were used to test the hypotheses. The findings showed a positive impact on the academic achievement of students who received peer instruction compared to those who did not. The study further deduced that students have a positive perception and attitude toward using peer instruction strategy in the learning of chemistry. It was recommended that secondary school teachers should adopt the use of peer instruction strategy.